Mental toughness. The psychological skills - Coogan, M. (Techniques Magazine, 2013)
Psychological characteristics such as mental toughness, goal setting, imagery, realistic performance evaluation and commitment have been shown to be the difference between a medal winner in the Olympics and non-medal winners (Abbot and Collins, 2003). Psychology plays an essential role in the ability of individuals to fulfill their athletic potential. This article will focus on mental toughness. Mental toughness is a broad subject that can be researched in many different ways. I will focus on what I believe are the most important components of mental toughness: the attributes that make up the belief system of a mentally tough athlete and the most important psychological skills needed for mental toughness.